(untitled) (American Journal of Islam and Society, 2015)
This book is a welcome addition to the ever-expanding literature on Muslim cosmopolitanism across the Islamicate world. Its chief aim is to decenter the long-held notion that cosmopolitanism was a style of thought that emerged primarily from the heart of Europe, beginning with the Greeks, and then carried over into the Enlightenment age of Emmanuel Kant and reached its full manifestation in the present moment (p. 2). Rather, “cosmopolitan instances,” which Kai Kreese deftly describes as “openness to the world (Weltoffenheit), experience of the world (Welterfahrung), and the skill to deal flexibly with the world (Weltgewandtheit)” (p. 33), took root in Muslim societies many centuries ago, particularly during the establishment of the Indian Ocean’s lively maritime Muslim community during the eleventh century ...